(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
The current research aims to identify the problems facing agricultural extension workers as facilitators in providing extension services to rural youth in the Baghdad Governorate. The research community included all agricultural extension workers (138) respondents (regardless of their specializations), and included workers in the Directorate of Agricultural Extension and Training, and its affiliated formations extension centers (2), extension farms (2), workers in the Agricultural Extension and Training Department in the Baghdad Agriculture Directorate, the Baghdad / Al-Karkh Agriculture Department in Abu Ghraib, and the Baghdad / Rusafa Agriculture Department, workers in the agricultural divisions in Baghdad/Al-Rusafa, (5 divisions), workers in the agricultural divisions in Baghdad/Al-Karkh (13 divisions|). Twenty (20) respondents were excluded from the research sample to conduct the initial test to measure the stability of the questionnaire. The initial questionnaire test was performed on a random sample of the agricultural divisions affiliated with the Baghdad Agriculture Directorate (Karkh/Rusafa), the Department of Agricultural Extension and Transfer Technologies, and the Extension Department in the Directorate, consisting of (20) respondents. The research data was collected using a questionnaire which included (42) items distributed over four areas: (financial and material problems, administrative and organizational problems, problems related to the work environment and relations, and problems related to the application of electronic agricultural extension services). Collected data was analyzed using the statistical analysis program SPSS, as well as using manual analysis using the Cronbach coefficient, the weighted mean, the percentage weight, and the hypothetical mean. The results of the research showed that the problems related to the work environment and relations came in first place, with a weighted mean of (3.60) degree and a percentage weight of (90.00) degree, then the problems related to the application of electronic agricultural extension services came in last order with a weighted mean of (3.39) degree and a percentage weight of (84.75) degree. Therefore, the researcher recommends the necessity of making efforts by agricultural extension institutions and relevant responsible authorities to prepare training programs to develop the capabilities of workers in the field of collective and participatory work to facilitate the provision of extension services to rural youth and provide support from through financial and moral incentives to achieve the facilitation role.